PENERAPAN BUSINESS JUDGMENT RULE DALAM TANGGUNG JAWAB DIREKSI BADAN USAHA MILIK NEGARA - Rr Ani Wijayati; Chris Anggi Natalia Berutu; Mawar Sitohang (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2025)
The Board of Directors of State-Owned Enterprises (BUMN) is an organ that has the duty and authority to carry out management and representation in and outside the court. In carrying out its management, the Board of Directors of State-Owned Enterprises has the principle of Business Judgment Rule in making business decisions that have an impact on the company in the future. Business Judgment Rule is a principle that protects the authority of directors in making business decisions. Directors are given flexibility and receive legal protection so that their decisions cannot be challenged even if this can cause state financial losses, but the doctrine often clashes with the characteristics of business that cannot be predicted and determined with certainty due to various influencing factors. This paper aims to analyze the application of the Business Judgment Rule principle known as the immunity doctrine to the business decisions of the Board of Directors of State-Owned Enterprises. Based on a literature review, this research concludes that the Business Judgment Rule has been implicitly regulated in Article 97 paragraph (5) of Law Number 40 of 2007 and Article 9F of Law Number 25 of 2025, but it is necessary to harmonize laws and regulations to understand the business judgment rule.